FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA SUB-SEKTOR MAKANAN DAN MINUMAN - Novvlerin Meldy; Herlin Tundjung Setijaningsih; Henny Henny (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The research conducted aims to see the effect of profitability and company size on company value. The population in this study is a food and beverage sub-sector listed on the IDX in 2019-2021. The sample collection technique was carried out using purposive sampling samples, with the number of sample data obtained as many as 26 from food and beverage sub-sector companies with a 3-year observation period so that the total sample was 61 data. The processing of this research data will be collected and processed using Microsoft Excel 2016 and using Statistical Package for the Social Science (SPSS) version 25. The result obtained on the basis of the research conducted is that profitability has a positive influence on the firm value and for this test it was also found that it was the firm size that had a significant negative influence on the firm value.